Construction of the Professional Identity in the Students of the Degree in Nursing - Abigail Contreras Oronzor; Ana Karen Galindo Flores; Nancy García Adriano; Erick Miguel Villalpando Velázquez; María de los Ángeles Godínez Rodríguez; Luis Alberto Regalado Ruiz (CuidArte)
Introduction. Professional identity is associated to the fact of having common experiences, ways of understanding and technical knowledge, as well as coinciding ways of perceiving problems and their viable solutions. Every professional requires an identity for the performance of their profession, this gives meaning to their actions and attitudes.Objective. Describe how the students of the Bachelor of Nursing at the School of Higher Studies Iztacala (FESI) build their professional identity throughout the career. Methodology. The present descriptive type research with qualitative approach and phenomenological method. It was carried out in the facilities of the FESI, the selection of the informants, was by typical ideal with five participants of eighth semester. A focus group session was conducted, this was audio recorded and later transcribed to digital format, the data obtained were processed and coded in three categories. Findings. Recognition, motivation and role models; the subcategories highlighted were: the figure of the teacher and the social recognition that are those that form and define the construction of the professional identity, the previous supports the theory of cognitive modeling-learning. Conclusions. Recognition is the main aspect that influences the formation of professional identity.